Pediatric palliative care - Trapanotto Manuela; Spizzichino Marco; Benini Franca; Ferrante Anna (BMC, 2008)
Abstract The WHO defines pediatric palliative care as the active total care of the child's body, mind and spirit, which also involves giving support to the family. Its purpose is to improve the quality of life of young patients and their families, and in the vast majority of cases the home is the best place to provide such care, but for cultural, affective, educational and organizational reasons, pediatric patients rarely benefit from such an approach. In daily practice, it is clear that pediatric patients experience all the clinical, psychological, ethical and spiritual problems that severe, irreversible disease and death entail. The international literature indicates a prevalence of incurable disease annually affecting 10/10,000 young people from 0 to 19 years old, with an annual mortality rate of 1/10,000 young people from birth to 17 years old. The needs of this category of patients, recorded in investigations conducted in various parts of the world, reveal much the same picture despite geographical, cultural, organizational and social differences, particularly as concerns their wish to be treated at home and the demand for better communications between the professionals involved in their care and a greater availability of support services. Different patient care models have been tested in Italy and abroad, two of institutional type (with children staying in hospitals for treating acute disease or in pediatric hospices) and two based at home (the so-called home-based hospitalization and integrated home-based care programs). Professional expertise, training, research and organization provide the essential foundations for coping with a situation that is all too often underestimated and neglected.